(a-3)(1+7)-2=14

Simple and best practice solution for (a-3)(1+7)-2=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a-3)(1+7)-2=14 equation:


Simplifying
(a + -3)(1 + 7) + -2 = 14

Reorder the terms:
(-3 + a)(1 + 7) + -2 = 14

Combine like terms: 1 + 7 = 8
(-3 + a)(8) + -2 = 14

Reorder the terms for easier multiplication:
8(-3 + a) + -2 = 14
(-3 * 8 + a * 8) + -2 = 14
(-24 + 8a) + -2 = 14

Reorder the terms:
-24 + -2 + 8a = 14

Combine like terms: -24 + -2 = -26
-26 + 8a = 14

Solving
-26 + 8a = 14

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '26' to each side of the equation.
-26 + 26 + 8a = 14 + 26

Combine like terms: -26 + 26 = 0
0 + 8a = 14 + 26
8a = 14 + 26

Combine like terms: 14 + 26 = 40
8a = 40

Divide each side by '8'.
a = 5

Simplifying
a = 5

See similar equations:

| 3x-12x^2+x-12=0 | | -9+-6= | | a-3=-15 | | 3-2x(x-1)=x(3-2x)-(x-3) | | -2(r+7)=-35 | | x^100+x^2+1=0 | | -1/4(x-12)+1/2(x+2)=x+4 | | 2(x-3)=9 | | 65-2x=43x+15 | | -5=3m-13 | | 12-2(y+5)=4(y-7)-(y-1) | | y=5Inx | | 6.1=7.7-0.8x | | 12y=2x-6 | | 3m+3=2m+4 | | 2(5x-4)=11x | | graphy+9=5(x+6) | | 2x-9=8x+3 | | 1/7(3x+2)-1/5(x+4)=2 | | 14=7x+6-5x | | 5(3x-1)=19 | | x(x-4)=221 | | 4x-3y=26 | | 8u+2=4u-10 | | b-1+3b=22 | | 0.2p-1.8=2.3p-4.5-1.8p | | 0.06x+0.03(100+x)=4.35 | | x^2000+x^1000-2=0 | | 3y^2-11y-10=0 | | 5-3x=3x+15 | | 5-3x=3x-15 | | 6(x+3)=2(x+27) |

Equations solver categories